2015
DOI: 10.4172/2155-6156.1000485
|View full text |Cite
|
Sign up to set email alerts
|

Gender Disparity in the Prevalence of Metabolic Syndrome in Korea: Results from the Korea National Health and Nutrition Examination Survey, 2012

Abstract: Objectives: To evaluate gender specific characteristics in the prevalence of metabolic syndrome (MetS) and abnormalities in Korean population using the 2009 Joint Interim Statement of the International Diabetes Federation. Methods: We performed a secondary analysis of data based on the 2012 Korea National Health and Nutrition Examination Survey (KNHANES). MetS prevalence was calculated for 5,935 Korean adults (≥ 20 years of age) by sex and age group. Incidence rates of five MetS risk factors were also assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
2
0
0
Order By: Relevance
“…Generally, however, all of these results support the existence of gender differences in the prevalence of MetS, and the conflicting results are likely due to differences in the age and ethnicity of the populations surveyed and the MetS definitions used. Our findings are consistent with those of previous reports (Adam et al, 2015;Chen et al, 2010;Im & Seomun, 2015) indicating significantly higher prevalence rates of hypertriglyceridemia, hypertension, and hyperglycemia in young adult males compared to young adult females, which researchers have attributed to variations in fat distribution, sex hormones, and ferritin levels (Jehn, Clark, & Guallar, 2004;Razzouk & Muntner, 2009). Premenopausal females have higher levels of estrogen than young adult males, which promotes insulin sensitivity, glucose homeostasis, favorable lipid profiles, less visceral fat accumulation (Geer & Shen, 2009;Pradhan, 2014), lower BP, and lower TG levels (Razzouk & Muntner, 2009).…”
Section: Prevalence Of Mets and Its Components By Gendersupporting
confidence: 94%
See 1 more Smart Citation
“…Generally, however, all of these results support the existence of gender differences in the prevalence of MetS, and the conflicting results are likely due to differences in the age and ethnicity of the populations surveyed and the MetS definitions used. Our findings are consistent with those of previous reports (Adam et al, 2015;Chen et al, 2010;Im & Seomun, 2015) indicating significantly higher prevalence rates of hypertriglyceridemia, hypertension, and hyperglycemia in young adult males compared to young adult females, which researchers have attributed to variations in fat distribution, sex hormones, and ferritin levels (Jehn, Clark, & Guallar, 2004;Razzouk & Muntner, 2009). Premenopausal females have higher levels of estrogen than young adult males, which promotes insulin sensitivity, glucose homeostasis, favorable lipid profiles, less visceral fat accumulation (Geer & Shen, 2009;Pradhan, 2014), lower BP, and lower TG levels (Razzouk & Muntner, 2009).…”
Section: Prevalence Of Mets and Its Components By Gendersupporting
confidence: 94%
“…In previous studies, researchers have found that males had a greater propensity for unhealthy lifestyle behaviors and were less motivated to engage in health-promoting activities than females, thus placing them at a higher risk of MetS (Chen, Wu, Hwang, & Li, 2010). Our result in the present study is consistent with the findings of a study involving Korean males aged 20-39 years in which young men had a higher prevalence of MetS than similarly aged women (Im & Seomun, 2015) but is inconsistent with reports of higher MetS prevalence in American females aged 20-39 years than in males of the same age (Aguilar et al, 2015). Generally, however, all of these results support the existence of gender differences in the prevalence of MetS, and the conflicting results are likely due to differences in the age and ethnicity of the populations surveyed and the MetS definitions used.…”
Section: Prevalence Of Mets and Its Components By Gendersupporting
confidence: 91%